Current philosophy in the surgical management of neck metastases for head and neck squamous cell carcinoma. Issue 6 (30th June 2014) - Coskun, H. Hakan; Medina, Jesus E.; Robbins, K. Thomas; Silver, Carl E.; Strojan, Primož; Teymoortash, Afshin; Pellitteri, Phillip K.; Rodrigo, Juan P.; Stoeckli, Sandro J.; Shaha, Ashok R.; Suárez, Carlos; Hartl, Dana M.; et al.
Abstract Neck dissection is an important treatment for metastases from upper aerodigestive carcinoma; an event that markedly reduces survival. Since its inception, the philosophy of the procedure has undergone significant change from one of radicalism to the current conservative approach. Furthermore, nonsurgical modalities have been introduced, and, in many situations, have supplanted neck surgery. The refinements of imaging the neck based on the concept of neck level involvement has encouraged new philosophies to evolve that seem to benefit patient outcomes particularly as this relates to diminished morbidity. The purpose of this review was to highlight the new paradigms for surgical removal of neck metastases using an evidence‐based approach. © 2014 Wiley Periodicals, Inc. Head Neck 37: 915–926, 2015